Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Ukuran Perusahaan dan Jumlah Dewan Komisaris sebagai Variabel Pemoderasi (Studi pada Perusahaan Manufaktur yang terdaftar Bursa Efek Indonesia) - Putri, Ayu Kemala; Sudarma, Made; Purnomosidhi, Bambang (Jurnal Aplikasi Manajemen, 2016)
Abstract: This study aims toanalyze the effect of CSR on firm value by examining the size of the company and the number of commissioners as a moderating variable. The population in this study is a manufacturing company that go public in the Indonesia Stock Exchange for the year 2012 which amounts to 131 companies. The samples used purposive sampling method with the approach of Judgment Sampling by the number of observed sample as many as 79 companies.Analysis of the data in this study using MRA (moderated regression analysis).The results showed that the value of the company is not affected by the Corporate Social Responsibility. the value of the companywill be affectedby corporate social responsibilityto be moderated by the size of the company and the number of commissioners. In the practice of Corporate Social Responsibility, is necessary alignment of the implementation of the substance of social welfare and environmental protect on so that in the long term will give a value for the company. In addition, have to balance between the number of commissioners and management, this is done to effectively perform its functions in terms of communicationcoordination and decision-making related to corporate social responsibility